The PEACE Portal - Revisiting the Sea of Stone - Saar, Ortal-Paz (My University, 2021)
At the DH Benelux conference of 2017 I presented a poster titled “A Sea of Stone: Digitally Analyzing Jewish Funerary Inscriptions”. The poster described a new digital initiative: an international portal of Jewish funerary culture, part of which would be epigraphic and explore epitaphs from the sixth century BCE to the present day. The portal has recently been launched (https://peace.sites.uu.nl/). It consists of four sections, of which the epigraphic one, containing over 40,000 inscriptions, is fully functional. This paper describes the PEACE portal focusing on its epigraphic section: content, aims, challenges and future goals.
Keywords: Digital Humanities; Funerary culture; Funerary inscriptions; Judaism